1984
DOI: 10.1523/jneurosci.04-12-02939.1984
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the direction of neurite growth by pulsed and focal electric fields

Abstract: We have studied the orientation of neurite growth in the culture of embryonic Xenopus neurons in response to three types of extracellular electric fields: spatially uniform pulsed fields, focally applied steady (DC) fields, and focally applied pulsed fields. Under uniform pulsed fields, neurites showed a preferential orientation toward the cathode pole of the field in a manner similar to that previously found for DC fields. The extent of neurite orientation depended upon the duration, amplitude, and frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(54 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…That is, in the Chat mutants, simply the overabun- dance of axons may force some into territory that they normally would not innervate. Consistent with the idea that ChAT/ACh plays a role in restricting the development of nerve terminals to the central band of muscle, Patel and Poo (1984) demonstrated that growth cones can be guided to, and will stop growing at, a focal electrical field. When the focal electrical field is turned off, growth cones resume migration away from the focal field.…”
Section: Discussionsupporting
confidence: 58%
“…That is, in the Chat mutants, simply the overabun- dance of axons may force some into territory that they normally would not innervate. Consistent with the idea that ChAT/ACh plays a role in restricting the development of nerve terminals to the central band of muscle, Patel and Poo (1984) demonstrated that growth cones can be guided to, and will stop growing at, a focal electrical field. When the focal electrical field is turned off, growth cones resume migration away from the focal field.…”
Section: Discussionsupporting
confidence: 58%
“…Another possibility for the sustained elevation in [Ca 2+ ] i might involve passive influx. It is estimated that in a cell of 10-m diameter, exposed to an EF of 100 mV/mm, the cathodal side of cell membrane would depolarise by ~5 mV, whereas the membrane facing the anode hyperpolarises by the same amount (Patel and Poo, 1982;Poo, 1981). Presuming the dependence of depolarisation and/or hyperpolarisation on electric field strength is linear, an electric field of 1000 mV/mm would cause the cathodal side of cell membrane to depolarise by ~50 mV, whereas the anodal side of membrane hyperpolarise by ~50 mV.…”
Section: Discussionmentioning
confidence: 99%
“…Passive influx It has been estimated that for dcEFs of 10-100 mV/mm applied to a cell 10 µm across, the cathodal side depolarizes by ∼5 mV whereas the membrane facing the anode hyperpolarizes by the same amount (Patel and Poo, 1982;Poo, 1981). This hyperpolarization could increase the electromotive force driving cations passively into the cell (Cooper and Keller, 1984).…”
Section: Dcef-mediated Direct Regulation Of [Ca 2+ ]Imentioning
confidence: 99%